Thrombospondin-platelet interactions. Role of divalent cations, wall shear rate, and platelet membrane glycoproteins. - Agbanyo, F R (1993)
The role of thrombospondin, a multifunctional matrix glycoprotein, in platelet adhesion is controversial: both adhesive and antiadhesive properties have been attributed to this molecule. Because shear flow has a significant influence on platelet adhesion, we have assessed thrombospondin-platelet interactions both under static and flow conditions. The capacity of thrombospondin to support platelet adhesion depended upon its conformation. In a Ca(2+)-depleted conformation, such as in citrated plasma, thrombospondin was nonadhesive or antiadhesive as it inhibited platelet adhesion to fibrinogen, fibronectin, laminin, and von Willebrand factor by 30-70%. In a Ca(2+)-replete conformation, however, thrombospondin effectively supported platelet adhesion. Shear rate influenced this adhesion; percent surface coverage on thrombospondin increased from 5.4 +/- 0.3 at 0 s-1 to 41.5 +/- 6.7 at 1,600 s-1. In contrast to the extensive platelet spreading observed on fibronectin at all shear rates, platelet spreading on thrombospondin occurred only sporadically and at high shear rates. GPIa-IIa, GPIIb-IIIa, GPIV, and the vitronectin receptor, which are all proposed platelet receptors for thrombospondin, were not solely responsible for platelet adhesion to thrombospondin. These results suggest that thrombospondin may play a dual role in adhesive processes in vivo: (a) it may function in conjunction with other adhesive proteins to maintain optimal platelet adhesion at various shear rates; and (b) it may serve as a modulator of cellular adhesive functions under specific microenvironmental conditions.